Diversity in boardroom and debt financing: A case from China - Sun, Xinbo; Ahmad, Muneeb; Tahir, Kamran; Zafar, Hammad (Frontiers in Psychology, 2022)
The study aims to explore the role of gender diversity in debt financing choices among Chinese listed firms. The study used the Chinese listed firm’s data from 1991 and 2022 from the Chinese Stock Market return. The study used the fixed effect regression analysis and revealed that gender diversity has positive effect on the debt financing among Chinese firms. Additionally mass theory results suggested that at least three females in the board have significant influence on firms and it served as the voice of gender diversity to influence the board decisions regarding the debt financing. The study has several theoretical and practical implications. The study stresses on the need of significant diversity in the board rather than one female presence in the board. Secondly this study contradicts with the stereo type perception about females that they are not taking the risky decisions.